NAH broadcasting systems - Adrianto, Christopher Reynard (2019)
NAH Broadcasting Systems (NAH-BS) aims to explore the common issues and trends of Generation Y through expressing the absurd nature of millennial entertainment, with the hope of inciting fellow millennials to reflect on our habits. Every generation has their own stereotypes, and Generation Y is no exception. As media plays a huge part in our lives, we are known to be screen-centric. We focus so much on our online public personas that our neurotic fixation on this has led to a variety of themes. Through this project, I hope to identify and explore these themes, such as the increased usage of suicidal jokes and self-deprecating humour. Millennials often seek for instant validation and one of our biggest fears is the fear of missing out. New terms such as slacktivism (minimum effort activism) and premium mediocre fashion (mid-range luxury items) are becoming increasingly prominent. Aside from these, millennials are also being pressured to perform from previous generations. Additionally, growing up in an environment of ‘participation medals’ has in turn distorted our understanding of success, failure and criticism. This project consists of a series of short advertisements/skits under the umbrella of a fictional network named NAH-BS. The network strives to express these weird traits in the light of absurdist humour. In this regard, I would like to invite millennials to stop and reflect upon these themes. As much as we like to fall back on these media forms available to us, do they do more harm than good? The project focuses on digital execution, as it is the medium that ties our generation together. The channel format is a medium of commentary of widespread distribution and advancements of screen technology. In essence, NAH-BS aims to engage and intrigue fellow millennials to take time, stop and reflect.